Complex Analysis - Busam, Rolf (Springer-Verlag Berlin Heidelberg, 2009)
Differential Calculus in the Complex Plane C -- Integral Calculus in the Complex Plane C -- Sequences and Series of Analytic Functions, the Residue Theorem -- Construction of Analytic Functions -- Elliptic Functions -- Elliptic Modular Forms -- Analytic Number Theory -- Solutions to the Exercises.
Includes bibliographical references and index
Keywords: Lehrbuch; Funktionentheorie